Jejunal cavernous lymphangioma. (12th May 2011) - Morris-Stiff, Gareth; Falk, Gavin A; El-Hayek, Kevin; Vargo, John; Bronner, Mary; Vogt, David P
Abstract : Cavernous lymphangiomas are usually identified in infants and children with the majority of lesions found around the head and neck, trunk or extremities. Tumours affecting the intra-abdominal organs are rare. The authors report a case of small bowel cavernous lymphangioma arising within the jejunum of a 34-year-old woman presenting with dyspnoea and anaemia, and review the existing literature relating to this uncommon tumour.